Tunable indium tin oxide thin film as saturable absorber for generation of passively Q-switched pulse erbium-doped fiber laser - Zalkepali, N U H H; Awang, Noor Azura; Yuzaile, Y R; Zakaria, Z; Latif, A A; Ali, A H; Mahmud, N N H E (Springer, 2020)
A tunable Q-switched pulse erbium-doped fiber (EDF) laser using indium tin oxide (ITO) thin-film-based saturable absorber (SA) is proposed and demonstrated. The SA is formed by depositing an ITO layer using DC magnetron sputtering on the fiber ferrule, which can be easily fabricated in less than 200 s with thickness of 17.80 nm. The proposed tunable Q-switched pulse EDF laser is operated from 1540.0 to 1570.0 nm, covering a total wavelength of 30.0 nm. The generated output pulses displayed a repetition rate range between 21.70 and 94.34 kHz. The shortest pulse width retrieved is 3.22 ls at the maximum pump power of 378.6 mW, while the maximum pulse energy recorded is 30.29 nJ. To the best of the authors’ knowledge, this appears to be the first proposed tunable passively Q-switched pulse EDF laser using ITO that serves as SA, which can promote ITO film in the application of ultrafast photonics.